The impacts of germinating organic wheat: effects on phytic acid, resistant starch, and functional properties of flour, and sensory attributes of sourdough bread. (22nd February 2021) - Stern, Alexandra L.; Berstein, Julia; Jones, Stephen S.; Blumberg, Jeffrey B.; Griffin, Timothy S.
Summary: This study assessed the impact of germination duration on two varieties of wheat grown organically (Expresso and Syngenta SY Basalt (Basalt)). In Expresso, d ‐glucose content increased from 0.06 g/100 g in the control to 0.55 g/100 g after a 24‐h germination period ( P < 0.05). In both varieties, similar increases were observed for sucrose and maltose, and no pattern emerged for resistant starch or phytate. In Basalt, baseline phytate (0 h 1.07 g/100 g) did not differ from treatment groups (6 h 0.97 g/100 g; 12 h 0.98 g/100 g; 24 h 1.09 g/100 g; 36 h 0.98 g/100 g). Functional properties of flour decreased with germination duration and resulted in bread which panellists perceived to have inferior crumb (24 h Expresso; 36 h Basalt; P < 0.05). However, there was no difference in the overall acceptability of breads across treatments and inclusion of germinated wheat improved bread sweetness. Abstract : This study assessed the impact of increasing germination duration on two organic wheat varieties. Despite inferior functionality at longer germination durations, there was no difference in overall sensory acceptability of breads. Increases in free sugar content improved bread sweetness, and could reduce the need for added sugars in whole wheat breads.